The representation and practice of healthcare integration: alterity and the construction of healthcare integration in the Philippines - Kadetz, P (2012)
Non-biomedical practices and practitioners serve as the primary source of healthcare for a majority of populations in low-income countries. The World Health Organization (WHO) has prioritised the integration of local non-biomedical healthcare practices and practitioners into formal state healthcare systems since the Declaration of Alma Ata in 1978. Heretofore, both WHO's representation of healthcare integration and its discourse of beneficence have been reified, yet largely unexamined. This research examines the processes of healthcare integration through qualitative research at multiple levels of analysis in the Philippines to better understand: what healthcare integration is; how stakeholders perceive healthcare integration; and how the practice of healthcare integration may differ from its discursive representation. This research was conducted in communities of four municipalities of the Philippines over a period of 22 months. The sample of 1,023 informants consisted of community members, community leaders, healthcare providers, and policy actors who participated in semistructured interviews, focus groups, and pile sorts. Participant experience was also conducted over a year-long period in both the Traditional Medicine Unit of The Western Pacific Region Office of the WHO and the Philippine Institute of Traditional and Alternative Healthcare of the Department of Health of the Philippines. The integration of local birth attendants through prohibition of their practices serves as a case example. From this research, healthcare integration is understood as multiple independent and interdependent processes that occur simultaneously across global, state, and local levels of analysis, including the individual level. However, community level stakeholders were identified to resist healthcare integration practices, which they perceived as either inappropriate for their community and/or capable of compromising their access to healthcare. These findings are presented in terms of the development studies discourses concerning appropriate knowledge/technology transfer, community agency, complex adaptive systems, health reform and administrative decentralisation, and the relevance of subjectivity in development interventions.